KEPEMIMPINAN KEPALA SEKOLAH DALAM TATA TERTIB BELAJAR SISWA - Edo Bramesta; Suwadi Suwadi (Jurnal Pendidikan, Kebudayaan dan Keislaman, 2023)
The Headmistress is one of the components of education that is influential in improving teacher performance. The success of school education is largely determined by the success of the principal in managing the educational staff available at school. This study generally aims to determine the principal's leadership in improving student learning discipline. This is in accordance with the regulations of the Minister of National Education where the principal is a teacher who is given additional duties as the principal of a school or madrasa to lead and manage a school or madrasa in an effort to improve student discipline. Managing a school or madrasah requires a professional leadership model and style. Implementation of school rules, factors that cause violations in the implementation of rules and regulations and school efforts to reduce the number of violations against the implementation of rules. The methodology of this research is to use literature review or library research, by collecting data from various sources, books, journals, and other analyses. The principal functions as a leader and manager in the school who has an important role in realizing the school's vision and mission.